Deuterium kinetic isotope effect studies of a potential in vivo metabolic trapping agent for Monoamine Oxidase-B - Drake, Lindsey R. (ACS Chem Neurosci, 2018)
Visualizing the in vivo activity of monoamine oxidase B (MAO-B) is a valuable tool in the ongoing investigation into astrogliosis in neurodegeneration. Existing strategies for imaging changes in MAO enzyme expression or activity have utilized the irreversible suicide inhibitors or high-affinity reversibly binding inhibitors as PET ligands. As an alternative approach, we developed 4-methyl-7-((1-[(11)C]methyl-1,2,3,6-tetrahydropyridin-4-yl)oxy)-2H-chromen-2-one ([(11)C]Cou) as a metabolic trapping agent for MAO-B. Trapping of [(11)C]Cou in rhesus monkey brain demonstrated MAO-B selectivity. In this work we have attempted to improve on the in vivo pharmacokinetics of [(11)C]Cou by using the deuterium kinetic isotope effect (KIE) to slow the MAO-B mediated oxidation step and thus reduce the rate of trapping in brain tissues. However, in vitro assays of enzyme kinetics and in vivo PET imaging of pharmacokinetics in primate brain showed no effects of deuterium substitution on the tetrahydropyridine ring of [(11)C]Cou. The results are possibly due to masking of the KIE by a second step in the overall metabolism of the new imaging agent.